2015
DOI: 10.15517/lank.v7i1-2.19569
|View full text |Cite
|
Sign up to set email alerts
|

Experimental reintroduction of the threatened terrestrial orchid Diuris fragrantissima

Abstract: Diuris fragrantissima D. L. Jones et M. A. Clem. is a perennial terrestrial orchid endemic to the state of Victoria, Australia. The species is listed as Critically Endangered in Victoria under the criteria of the International Union for the Conservation of Nature and Natural Resources (IUCN), having suf- fered a severe population decline since the 1930s, largely attributable to habitat destruction for agricul- tural and urban development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…There were significant differences in average fresh weight of germinated seeds (Figure 5B), average developmental stage (Figure 5C), proportions of seeds with high developmental stage (stage 6) (Figure 5D, E) and shriveled seeds (Table 1) between self-pollination and nectar addition under the conditions of symbiotic and asymbiotic cultures, suggesting that nectar addition partially results in geitonogamy. It is important for orchids to reach higher developmental stage faster under natural conditions to enhance its survival and resistance to disadvantageous environmental and climate conditions (Smith et al, 2007;Stewart, 2008). Based on this conclusion, and combined with our study results, it is confirmed that germinated seeds after cross-pollination and natural conditions have higher ability to adapt to the environment than that after self-pollination and nectar addition.…”
Section: Discussionmentioning
confidence: 99%
“…There were significant differences in average fresh weight of germinated seeds (Figure 5B), average developmental stage (Figure 5C), proportions of seeds with high developmental stage (stage 6) (Figure 5D, E) and shriveled seeds (Table 1) between self-pollination and nectar addition under the conditions of symbiotic and asymbiotic cultures, suggesting that nectar addition partially results in geitonogamy. It is important for orchids to reach higher developmental stage faster under natural conditions to enhance its survival and resistance to disadvantageous environmental and climate conditions (Smith et al, 2007;Stewart, 2008). Based on this conclusion, and combined with our study results, it is confirmed that germinated seeds after cross-pollination and natural conditions have higher ability to adapt to the environment than that after self-pollination and nectar addition.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al . (2007) have noted that soil aeration through tilling may encourage persistence of mycorrhizal fungi in soils previously compacted through agricultural practices, and hence the reworking of soil through the practice of mine rehabilitation has likely improved micro‐habitat for these fungi.…”
Section: Discussionmentioning
confidence: 99%
“…As in this case, such a situation can be averted by translocating fungi within soil cores with translocated orchids, allowing them to spread within replaced topsoil. Smith et al (2007) have noted that soil aeration through tilling may encourage persistence of mycorrhizal fungi in soils previously compacted through agricultural practices, and hence the reworking of soil through the practice of mine rehabilitation has likely improved micro-habitat for these fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Several Sunshine Diuris reintroductions were conducted within the Port Phillip Region of Victoria by DSE with Parks Victoria, ANOS and local government. A major reintroduction trial of 700 plants was conducted as part of a PhD (Smith et al 2007), which focused on why previous reintroductions of the species were apparently unsuccessful.…”
Section: Sunshine Diuris (Diuris Fragrantissima)mentioning
confidence: 99%
“…Research is the key to conducting successful orchid conservation projects within Victoria. The RBGM in conjunction with several Universities and DSE has hosted many postgraduate projects on orchid conservation (Marvern, 1996;Wright 2007;Smith et a/ 2007). Recently collaborations between Melbourne University, RMIT University, the Wimmera CMA (WCMA) and the RBGM have explored taxonomic relationships of some of the orchid mycorrhiza.…”
Section: Introductionmentioning
confidence: 99%